The pyroclastic komatiite complex at Sattasvaara in northern Finland - M. Saverikko (Bulletin of the Geological Society of Finland, 1985)
The Sattasvaara komatiite complex is part of an extensive zone of explosive komatiitic volcanism which may have been a significant stage in the Lapponian evolution regarded as Archean. This volcanism took place at the latest 2.43 Ga ago and appears to have been connected with cratonic rifting in the Baltic Shield. The complex was formed by fissure eruptions rather than central-vent eruptions, at the margin of a restricted depositional basin. Effusive, explosive and mixed eruption phases were separated by erosional periods and the komatiitic volcanism was succeeded by mafic effusions and explosive eruptions. The Sattasvaara complex is composed of interchanging amphibole rocks, or komatiitic basalts, and amphibole-chlorite rocks or (basaltic)komatiites, and encloses minor serpentinitic and peridotitic rocks as terminal komatiite flows and picrite plugs. However, main part of the komatiites has discharged earlier and is present as intercalations in graphitic slate zone beneath the Sattasvaara complex. The komatiitic rocks were originally co-magmatic according to their gradual rock suite. The komatiitic basalt (MgO 9‒18 wt.% anhydrous basis) shows signs of fractional crystallization of pyroxene and plagioclase, whereas the (basaltic) komatiite (MgO 18‒29 wt.% anhydrous basis) contains pyroxene and olivine phenocrysts and the komatiite (MgO>29 wt.% anhydrous basis) is olivine-pyroxene cumulate both in distinct flows and lower parts of the (basaltic)komatiite flows. The erupting lavas differed physically and discharged in unlike manner: eruptions of the fluid komatiitic basalt were Hawaiian-type and the ones of the viscous (basaltic)komatiite were Strombolian-type. The initial komatiite flows were most fluidal and flowed after the manner of flood eruptions. Pyroclasticity is associated with the (basaltic)komatiite that is dominantly fragmentary, consisting of lithic, vitric and crystal ejecta; subordinate lava flows are largely block lavas. The voluminous explosive eruptions appear to have been magmatic in origin. ...